DAMPAK KEPENDUDUKAN TERHADAP PEMUKIMAN - Muhadjir Darwin (Populasi, 1991)
Housing and its sanitation has been widely recognized as a global human problem. Apart of the sources of problem is population, i.e high rate of population growth and over urbanization. Using the Indonesian case, this paper discusses the relationship between population and housing. The population growth rate of Indonesia declined from 2.3 annually during the decade of 1971- 1980 to 1.97 annually during the next decade. However, the average number of household members declined from 4.9 to 4.5 during the same period. As a result, the number of households increased substantially than the number of population. This phenomenon will affect the increase of the need of housing. In the meantime, the economic condition of Indonesian households could not compete with the soaring prices of housing. In addition, government capabilities to provide housing for the society are still very limited. The data available shows the evidence onthe scarcity of housing,where the number of housing stock is smaller than the number of households. However, The number of housing stock has increased substantially, whereas the difference between the number of households and the number of housing stock decreased consistently. These data indicate that productivity of housing market, particularly the informalone, isconsiderably high, even thoughinreality the qualityof suchhousing is, ingeneral, low.